Set new hires up for success with the right orientation program - Davis, Alison (Alison Bonnie), 1957- (FT Press Delivers elements., 2011)
This Element is an excerpt from The Definitive Guide to HR Communication: Engaging Employees in Benefits, Pay, and Performance (9780137061433) by Alison Davis and Jane Shannon. Available in print and digital formats. Build an orientation process that systematically improves the odds that your new employees will succeed! You've just hired a terrific person. The bad news: There's a good chance your new employee won't work out. According to a study by Leadership IQ, only 19% of new hires achieve unequivocal success within 18 months. To increase your odds, build an effective orientation process and program. Traditionally, HR focuses on the orientation session. That's vital, but not enough...